Performance Improvement of Active Power Filter under Distorted and Unbalanced Grid Voltage Conditions - Biricik, S.; Ozerdem, O. C.; Redif, S.; Kmail, M. I. O. (Elektronika ir Elektrotechnika, 2013)
In the case of balanced and undistorted supply voltages, shunt APFs can achieve current harmonic cancellation and give unity power factors. However, this is not possible when grid voltage is non-sinusoidal and unbalanced. In this paper, we first show that the harmonic suppression performance of the well-known p-q theory deteriorates in non-ideal grid voltage conditions. A technique for alleviating the detrimental effects of a distorted and unbalanced grid voltage is proposed that uses a self-tuning filter with p-q theory. The proposed control technique gives an adequate compensating current reference even for non ideal voltage condition. The results of simulation study are presented to verify the effectiveness of the proposed control technique in this study. DOI: http://dx.doi.org/10.5755/j01.eee.19.1.3247